2018
DOI: 10.1111/his.13705
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Fra‐1, c‐Jun and c‐Fos in odontogenic keratocysts: potential correlation with proliferative and anti‐apoptotic activity

Abstract: This study revealed for the first time that Fra-1, c-Jun and c-Fos were overexpressed in OKCs and had a close correlation with proliferation and anti-apoptosis potential of OKCs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…Interestingly, the role of Fos in apoptosis appears to be diverse. Some studies suggested that Fos can reduce apoptosis, while others suggest that Fos can increase apoptosis ( 34 , 39 – 41 ). Our study found that knockdown of Fos can reduce cell survival rate, increase Bax/Bcl-2 ratio, and increase ATP content, which means knockdown of Fos increases neuron apoptosis after OGD.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the role of Fos in apoptosis appears to be diverse. Some studies suggested that Fos can reduce apoptosis, while others suggest that Fos can increase apoptosis ( 34 , 39 – 41 ). Our study found that knockdown of Fos can reduce cell survival rate, increase Bax/Bcl-2 ratio, and increase ATP content, which means knockdown of Fos increases neuron apoptosis after OGD.…”
Section: Discussionmentioning
confidence: 99%
“…Fos is a member of the Fos protein family, which can be induced by hormones, growth factors, cytokines, heat shock, and oxidative stress. Fos and Jun proteins comprise a heterodimer namely AP-1 (activator protein 1, AP-1), an important transcription factors involved in apoptotic pathway and TNFrelated signaling pathway [49,50] . Thereby AP-1 plays an important role in pathological processes such as proliferation, differentiation, apoptosis, and inflammation of cells [51,52] .…”
Section: Discussionmentioning
confidence: 99%
“…Fos is a member of the Fos protein family, which can be induced by hormones, growth factors, cytokines, heat shock, and oxidative stress. Fos and Jun proteins comprise a heterodimer namely AP-1 (activator protein 1, AP-1), an important transcription factors involved in apoptotic pathway and TNF-related signaling pathway [49,50] . Thereby AP-1 plays an important role in pathological processes such as proliferation, differentiation, apoptosis, and in ammation of cells [51,52] .…”
Section: Discussionmentioning
confidence: 99%